Frontispiz: Anomalously Large Antiphase Signals from Hyperpolarized Orthohydrogen Using a MOF‐Based SABRE Catalyst. (7th February 2023) - Alam, Md Shahabuddin; Li, Xinlin; Brittin, Drew O.; Islam, Saiful; Deria, Pravas; Chekmenev, Eduard Y.; Goodson, Boyd M.
Abstract : NMR Spectroscopy . In their Communication (e202213581 ), Boyd M. Goodson et al. report the addition of parahydrogen to particles comprised of an iridium‐based catalyst on a metal‐organic framework to produce orthohydrogen. A strongly hyperpolarized state is achieved.